STUDY ON THE BIOLOGY OF JOHNIEOPS VOGLERl (SLEEKER) OF BOMBAY WATERS - Muthiah, C (Indian Journal of Fisheries, 2011)
Johnieops vogleri in Bombay waters attains an average size of 158 mm, 240 mm and 290 mm at the end of 1, 2 and 3 years as shown by the length-frequency method, and 164.4, 220.6 and 276.6 mm as indicated by the scales. The time of annulus formation in the scales was during May to September which coincides with low intensity of feeding, spawning activities of the fish and the prevailing monsoon. Juveniles prefer crustaceans and, as they grow, show the piscivorous tendency. Lower intensity of feeding is noticed during the spawning season. Fifty percent of the fish mature at 159 mm in length. The relative condition of the fish is correlated to the spawning activities. Fecundity varied from 26,028 to 581,298 eggs. The distribution of sexes observed during different months of the year is not significant except during October and November. Among 130-179 mm size groups, males preponderated, whereas females were more among 220-249 mm size groups.